Establishment of Apomixis in Diploid F2 Hybrids and Inheritance of Apospory From F1 to F2 Hybrids of the Ranunculus auricomus Complex - Barke, Birthe H.; Daubert, Mareike; Hörandl, Elvira (Frontiers in Plant Science, 2018)
Hybridization and polyploidization play important roles in plant evolution but it is still not fully clarified how these evolutionary forces contribute to the establishment of apomicts. Apomixis, the asexual reproduction via seed formation, comprises several essential alterations in development compared to the sexual pathway. Furthermore, most natural apomicts were found to be polyploids and / or hybrids. The Ranunculus auricomus complex comprises diploid sexual and polyploid apomictic species and represents an excellent model system to gain knowledge on origin and evolution of apomixis in natural plant populations. In this study, the second generation of synthetically produced homoploid (2x) and heteroploid (3x) hybrids derived from sexual R. auricomus species was analyzed for aposporous initial cell formation by DIC microscopy. Complete manifestation of apomixis was determined by measuring single mature seeds by flow cytometric seed screen. Microscopic analysis of the female gametophyte formation indicated spontaneous occurrence of aposporous initial cells and several developmental irregularities. The frequency of apospory was found to depend on dosage effects since a significant increase in apospory was observed, when both F1 parents, rather than just one, were aposporous. Other than in the F1 generation, diploid Ranunculus F2 hybrids formed BIII seeds and fully apomictic seeds. The results indicate that hybridization rather than polyploidization seems to be the functional activator of apomictic reproduction in the synthetic Ranunculus hybrids. In turn, at least two hybrid generations are required to establish apomictic seed formation.